Pluralism, Religion, and Secularism - Yinger, John Milton (Journal for the scientific study of religion, 1967)
Disagreements over definitions and consequent difficulties in precise measurement have obscured the study of the relationships among pluralism, religion, and secularism. But the importance of those relationships requires that we attempt to explore them. An emphasis on pluralism, it is suggested, supports religious freedom and tolerance, but it may also support rigidity in religious traditions. Defense of separate religious communities may transfer questions of social integration to secular institutions that are at least potentially anti-religious; or it may promote anomie. Substantial amounts of secularism, so often defined as antithetical to religion, may actually be essential if religiously pluralistic societies are to escape high levels of conflict. Thus religiously heterogeneous societies are confronted with serious dilemmas. The numerous and subtle relationships among pluralism, religion, and secularism call for careful analysis.